Campylobacter jejuni-Associated Hemophagocytic Lymphohistiocytosis and Guillain-Barre Syndrome: A Case Report - Shi, Fang-e; Chen, Mei-fang; Li, Yong-jie; Dong, Gui-ying; Zhu, Ji-hong (Frontiers in Medicine, 2022)
Campylobacter jejuni (C. jejuni), a Gram-negative bacterium, belongs to microaerobic bacteria. We reported a 21-year-old male patient diagnosed with hemophagocytic lymphohistiocytosis (HLH) due to C. jejuni infection, who presented with multiple clinical manifestations of peripheral nerve injury, such as ophthalmoplegia, facial paralysis, and urinary retention during the treatment. Electromyography showed neurogenic injury and the final diagnosis was Guillain-Barre Syndrome (GBS). After treatment of dexamethasone combined with immunoglobulin, the patient was discharged from the hospital with partial recovery of neurological symptoms.